Fabric tensor and constitutive equations for a class of plastic and locking orthotropic materials - Jemioło, S.; Telega, J.J. (Archives of Mechanics, 1997)
The aim of the paper is to provide a general and common mathematical structure for a class of orthotropic materials undergoing plastic deformations or exhibiting locking behaviour. The orthotropy is included by using a fabric tensor. The tensorial constitutive relationships are studied from the point of view of tensor functions representations. Specific cases are also discussed.